Product and Service Quality Analysis: An Empirical Study of Customer Satisfaction in a Bakery - Nindiani, Aina; Hamsal, Mohammad; Purba, Humiras Hardi (Bina Nusantara University, 2018)
This research aimed to analyze the performance of a bakery located in Bekasi from the customer satisfaction on product and service quality. The method applied was Importance-Performance Analysis (IPA). IPA was conducted to determine the status of indicators related to product and service quality. It was to provide input to management in taking strategic actions. The sample size was 127 respondents. The used technique was non probability sampling. The results reveal that the priority of improvement is the taste indicator for product quality. On the other side, courtesy indicator is the priority for service quality that occupies position in Quadrant A. Hence, the bakery should emphasize those indicators as improvement priorities.